BUSINESS PROCESS MODELING TO IMPROVE THE ENTERPRISE MANAGEMENT SYSTEM - СHORNA, LUDMILA; GONCHAR, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article contains the results of research on the feasibility of modeling business processes. The modeling procedure itself is necessary to determine the level of efficiency of each business process, identify duplication of operations, a clear understanding of the roles of each participant and owner of the process. Business processes can be divided into production and management. Coverage of the quality system of the enterprise of all areas of activity involves modeling and analysis of each business process at all stages of the life cycle of the enterprise. The availability of various information systems for modeling, optimization and participation in enterprise management facilitates the work of analysts, but requires the definition of uniform rules and a clear reflection of information flows in modeling. The results of modeling are a clear visualization, a description of the process. The documentation contains the sequence of all procedures, their provision and control. Models allow you to detect redundancies and duplication, as well as clearly defined moments of beginning, end, transition from one process to another. The proposed concept combines a strategy based on a balanced system and detail of each process. The implementation of this concept is individual for each individual enterprise. The relevance of research is also confirmed by the need to form management hierarchical links between enterprise development strategy and business processes models of management, production and provision of services, management interaction and information flows. Among many concepts of using business process models, the most developed is the concept of business process management, which is based on the use of BPM-systems in the enterprise. This approach involves the formation of business process models in accordance with the process approach, their definition, design, documentation, measurement to achieve target results in accordance with the strategic objectives of the enterprise. The disadvantages of this approach are the difficulty of adaptation and the insufficient level of use of all digitalization tools in enterprises. The concept of mirrors involves the use of at least three mirrors for modeling - the actual business processes and their analysis, ideal processes in accordance with the strategy and quality system, optimized processes in accordance with the capabilities of the enterprise at the moment. The most adapted combination of strategic and process management is to create a balanced system of indicators in the main areas of enterprise development. For example, the following projections can be defined as: Production (production business processes), Personnel (personnel and corporate culture management processes), Finance (financial management processes), Orders (order management processes). For each of these projections will be formed special relevant indicators. The level of business processes is clearly distributed in a hierarchy - from strategy to customer and, according to the characteristics of production or services varies at each level. This analysis allows you to form each level of monitoring and control of the business process in order to optimize it. In addition, the introduction of new management and information technologies will make changes from strategic goals to each individual business process. For example, with the introduction of lean production, it is planned to make changes in the development strategy of the enterprise, in particular the restructuring of production processes and retraining of personnel. The result is the optimization of business processes and improving the efficiency of production resources. Such a restructuring project provides for variable modeling of business processes taking into account the qualifications of staff. The resulting models are the basis for determining the baseline that will be implemented and implemented. Monitoring, evaluation of business processes and projections is carried out periodically. Business process modeling, analysis and optimization are well-known procedures for process management, which is actively used for manufacturing enterprises. Analysis of the life cycle of the enterprise shows that each of its phases requires a reassessment of strategic indicators and business processes. This approach allows you to combine the strategy of enterprise development and its business processes. Known modeling techniques and tools based on information technology can be used for modeling, analysis and optimization, provided the formation of adapted model templates for each individual enterprise. Among the known concepts of using business processes, the most relevant are the use of quality management system and the formation of three mirror models of production and management processesThe proposed concept can be implemented using a system of balanced scores and a variety of information technology tools, provided clear algorithms for the interaction of management and information system of the enterprise.
Keywords: enterprise management; management; business process; business process management